The “Guamúchil” cultivation in a Mexican cultural landscape: A wild food source for people and birds - Ortega-Álvarez, Rubén; Pacheco-Flores, Alana; Casas, Alejandro (Frontiers in Forests and Global Change, 2022)
Indigenous management of biocultural resources can influence behavior of non-target animals. Hence, identifying shared resources between indigenous communities and fauna is essential to understand the ecological relationships that occur within cultural landscapes and promote sustainable practices. In this ethnoecological research we analyzed the feeding importance of a wild food that is used by both people and birds. We employed unstructured interviews and a survey to learn about food resources used by people of a Nahua community in western Mexico. Trees were frequently mentioned by locals; thus, we determined salience and cultural meaning of arboreal feeding sources for the indigenous community. The “Guamúchil” or Manila tamarind (Pithecellobium dulce) was the most bioculturally salient tree for the feeding and economy of local people, and we evaluated its significance for birds too. We analyzed avian foraging behavior to estimate the number of species that used the tree as a food source, the relevance of Guamúchil as foraging substrate, food types provided by this tree, and the avian feeding use of Guamúchil when it was locally employed as a live fence. We observed that local people tracked fruiting Guamúchil across the landscape and cultivated it in homegardens to facilitate fruit access. Seed pods were locally appreciated for direct consumption by households and commercialization. Guamúchil’s cover was low in the surrounding forest (mean: 0.4, standard deviation: 0.7), but much higher in homegardens (mean: 20.9, standard deviation: 16.3). We estimated that about a fourth of the avian species that foraged across the cultural landscape during our sampling feed on Guamúchil. Birds prey on invertebrates associated with this tree, but Guamúchil was mostly important to avian foraging for the fruit it produces. We determined that live fences of Guamúchil functioned as complementary food sources to birds. Our research shows how humans and birds share key feeding resources within cultural landscapes. Also, we depict how indigenous agroforestry practices positively impact wildlife foraging, which should be promoted as conservation and restoration tools to support sustainability. Identifying key foods and analyzing their use might facilitate the development of activities aimed to benefiting both humans and animal communities.